Using pegylated interferon alfa-2b and ribavirin to treat chronic hepatitis patients infected with hepatitis C virus genotype 1: Are nonresponders and relapsers different populations? - Silva, Giovanni Faria [UNESP]; Polonio, Rodrigo Jose [UNESP]; Pardini, Maria Ines de Moura Campos [UNESP]; Corvino, Silvia Maria; Saccomano Henriques, Rita Maria; Peres, Mari Nilce [UNESP]; Silveira, Liciana Vaz de Arruda [UNESP]; Coelho, Kunie Iabuki Rabello [UNESP] (Contexto, 2007)
The combination of pegylated interferon (PEG-INF) and ribavirin is currently the best treatment for chronic hepatitis C, providing a sustained virological response (SVR) in 54%-63% of patients. In patients infected with hepatitis C virus (HCV) genotype 1, the SVR rate is 42%-52%. To evaluate the treatment efficacy of this drug combination, we conducted an open, prospective study of 58 consecutive treatment-naive patients infected with HCV genotype 1 and treated at a university hospital, comparing those presenting an SVR (SVRs), nonresponders (NRs), and relapsers (RELs). Among the intent-to-treat patients, an end-of-treatment virological response was achieved in 69 % of the sample as a whole and in 52 % of the SVRs. We found that being an SVR was significantly associated with mild fibrosis (p = 0.04) and with undetectable HCV RNA at weeks 12 and 24 of treatment (p < 0.0001). Comparing the SVR and REL groups, we observed that being older than 40 was significantly associated with being a REL (p = 0.04). Being an NR was found to be associated with severe fibrosis and moderate inflammatory infiltrates (portal or periportal). In the polytomous logistic regression, no independent factors were associated with the REL group when compared with the SVR group. We conclude that RELs and NRs differ in comparison with SVRs. The RELs accounted for 17% of the sample. The HCV RNA test results at weeks 12 and 24 of treatment, although independent predictors of non-response (OR: 4.8 and 8.2, respectively), did not differ between SVRs and RELs.
Keywords: hepatitis C; pegylated interferon alfa 2b; genotype 1; relapsers